2019
DOI: 10.1186/s12943-019-0947-9
|View full text |Cite|
|
Sign up to set email alerts
|

Long non-coding RNA PVT1 promotes tumor progression by regulating the miR-143/HK2 axis in gallbladder cancer

Abstract: Background The long non-coding RNA PVT1 (lncRNA PVT1) has been reported to act as an oncogenic regulator of several cancers. However, its expression and function in gallbladder cancer (GBC) remain largely unknown. Methods In situ hybridization (ISH) and quantitative real-time PCR (qPCR) were performed to detect the expression of PVT1 and miR-143 in GBC tissues and cell lines. Immunohistochemistry (IHC) assays were performed to assess the expression of the hexokinase 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
261
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 315 publications
(267 citation statements)
references
References 33 publications
6
261
0
Order By: Relevance
“…For example, the lncRNA activated by TGF-b (lncRNA-ATB) upregulated EMT factors by competitively binding the miR-200 family in hepatocellular carcinoma invasion and metastasis [27]. PVT1 played as a miR-143 sponge and upregulated hexokinase 2 (HK2) expression levels in gallbladder cancer [13]. In this study, we demonstrated LINC00115 as a new miRNA sponge of miR-200 family to promote ZEB1 signaling in GBM.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, the lncRNA activated by TGF-b (lncRNA-ATB) upregulated EMT factors by competitively binding the miR-200 family in hepatocellular carcinoma invasion and metastasis [27]. PVT1 played as a miR-143 sponge and upregulated hexokinase 2 (HK2) expression levels in gallbladder cancer [13]. In this study, we demonstrated LINC00115 as a new miRNA sponge of miR-200 family to promote ZEB1 signaling in GBM.…”
Section: Discussionmentioning
confidence: 77%
“…High TGF‐β activity confers poor prognosis in glioma patients . TGF‐β1 promotes the self‐renewal of glioma‐initiating cells (GICs) through induction of LIF or Sox2 , and inhibition of TGF‐β activity decreases the CD44 high /ID1 high GIC population through inhibition of ID1 and ID3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical staining was performed was performed according to previously described method . In brief, the TMA slides were deparaffinised through xylene, antigen retrieved and blocked with bovine serum albumin.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical staining was performed was performed according to previously described method. 22 In brief, the TMA slides were deparaffinised through xylene, antigen retrieved and blocked with bovine serum albumin. Subsequently, the slides were incubated in ZNRD1 antibody diluted 1:200 at 4°C overnight and carried out using the EnVision™ system (DAKO) according to the manufacturer's instructions.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%